Penile Mondor's in a Covid-19 patient on prophylactic anti-thrombosis with rivaroxaban: a case report - Eren, Murat Tugrul; Ozveri, Hakan; Kurtoglu, Hilal (SPRINGER, 2021)
Background Penile Mondor's disease (PMD) is thrombophlebitis of the superficial dorsal vein of the penis. Following the occurrence of thrombotic events in the affected veins, the lumen often becomes occluded with fibrin and inflammatory cells. A hyper-coagulative state is one of the underlying causes although most cases of PMD are idiopathic. Coronavirus disease-2019 infection (COVID-19) is associated with frequent thrombotic events. Inflammation and thrombosis play a central role in the course and outcome of COVID-19, which can predispose to both venous and arterial thromboembolism. In this report, we present a 33-year-old male patient diagnosed with PMD during the subacute phase of COVID-19 infection while on prophylactic antithrombotic treatment. Case Presentation A 33-year-old male patient was diagnosed as PMD which occurred during the subacute phase of COVID-19 infection, while he was on active treatment of COVID-19 by prophylactic antithrombotic Rivaroxaban 15 mg therapy and curative antiviral medication. There was no recent sexual intercourse or trauma to the genitals. His PCR test for COVID-19 had become negative, and antibody test was positive at the time of his PMD's onset. Rivaroxaban was replaced by Enoxaparin (8000 IU/0.8 ml.), a low molecular weight heparin administered subcutaneously and twice daily. On the third day of this medication, all coagulative measurements returned to normal. PMD disappeared in the second week. Conclusion Low-dose Rivaroxaban 15 mg is not safe for some COVID-19-associated thromboembolism prophylaxis, and careful follow-up is critical due to the possibility of a wide range of pathologic thrombotic manifestations in COVID-19 infection.
Keywords: COVID-19; Drugs and medicines; Venous thromboembolism